System Information Vacancy Work In Palembang City Based On Codeingiter Framework - Muhammad Fauzan Ar-raafi; Dedi Haryanto; Apriansyah, Apriansyah (Jurnal Info Sains : Informatika dan Sains, 2024)
The rapid development of information technology has encouraged various sectors, including the world of work, to adapt to more modern and efficient systems. Accurate data management and the use of technology such as computers are now a must, especially amidst the demands of globalization and economic dynamics. In this context, websites emerge as relevant media for conveying information, including job vacancies. Currently, the challenges in finding jobs and meeting workforce needs are major problems experienced by many levels of society. Although the recruitment process has been digitized, there is still a gap between the number of vacancies available and qualified job seekers. To overcome this obstacle, the development of a web-based job vacancy information system is considered an effective solution. This system accelerates the dissemination of job vacancy information and facilitates access for job seekers and companies in the recruitment process. This study uses direct observation methods at the Palembang Multipurpose Building and literature studies from various literature for system development. This system is designed using the SDLC model, including the Waterfall and Agile methods, which ensure a structured and flexible development process. The results of this study indicate that the implementation of a web-based job vacancy information system can improve recruitment efficiency, provide wider access for job seekers in Palembang, and help companies get suitable candidates. This system is expected to be an effective means of connecting applicants with job opportunities more easily, quickly and efficiently.